2016
DOI: 10.1007/s10924-016-0883-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Polyesters from Waste Grapeseed Oil: Comparison with Soybean and Rapeseed Oils

Abstract: The aim of this study was to investigate the application of grapeseed oil, a waste product from the wine industry, as a renewable feedstock to make polyesters and to compare the properties of these materials with those derived from soybean and rapeseed oils. All three oils were epoxidized to give renewable epoxy monomers containing between 3.8 and 4.7 epoxides per molecule. Polymerisation was achieved with cyclic anhydrides catalysed by 4-methyl imidazole at 170 and 210°C. Polymers produced from methyl tetrahy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Although the TAG fingerprint of grapeseed A had a high similarity to that of the standard grapeseed oil (cos θ = 0.984), it was more similar to those of the soybean oils, as inferred by the network. In this case, it might be the consequence that soybean oil and grapeseed oil had similar FA chain compositions in TAGs, in which C18:2 FA was the most dominant species followed by C18:1 FA and C16:0 FA . For olive E, interestingly, it had a distinct TAG fingerprint (Figure S9).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the TAG fingerprint of grapeseed A had a high similarity to that of the standard grapeseed oil (cos θ = 0.984), it was more similar to those of the soybean oils, as inferred by the network. In this case, it might be the consequence that soybean oil and grapeseed oil had similar FA chain compositions in TAGs, in which C18:2 FA was the most dominant species followed by C18:1 FA and C16:0 FA . For olive E, interestingly, it had a distinct TAG fingerprint (Figure S9).…”
Section: Resultsmentioning
confidence: 97%
“…In this case, it might be the consequence that soybean oil and grapeseed oil had similar FA chain compositions in TAGs, in which C18:2 FA was the most dominant species followed by C18:1 FA and C16:0 FA. 40 For olive E, interestingly, it had a distinct TAG fingerprint (Figure S9). As a result, it had a relative low TAG similarity compared to other oils and thus presented as an independent node in the network.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Water samples: Water samples were processed as described by Kerubo et al (2020). Sediment samples: Samples were transferred onto aluminium foil and dried separately at 60° C (Clark et al, 2017) until a constant mass was attained. The dry samples were homogenised, weighed, and screened over sieves of 5mm and 500 µm mesh sizes on a shaker to obtain 500 -4999 µm size grains.…”
Section: Sample Processing and Microplastic Extractionmentioning
confidence: 99%
“…Grape seed oil was compared with soybean and rapeseed oil for producing renewable crosslinked polyester resins by Clark et al [106]. They concluded that grape seed oil presented a lower crosslink density due to its higher linoleic acid content but a higher thermal stability, being this product a viable substitute of traditional polyester resins in low stress or highdemanding thermal applications.…”
Section: Other Non-food Applicationsmentioning
confidence: 99%